A Bibliometric Study of Global Research Trends on Dyscalculia - Najwa Olifia Annnisa Rambe; Rohati Rohati; Duano Sapta Nusantara (Journal of General Education and Humanities, 2026)
Dyscalculia is a mathematics learning disability that is receiving increasing attention in international research. However, systematic mapping of the development and direction of global research in this field remains limited. Therefore, this study aims to analyze global research trends on dyscalculia from 2020 to 2025 by examining publication dynamics, thematic structure, and collaboration patterns among researchers and countries. This study employed a bibliometric approach with data obtained from the Scopus database. The analysis was conducted using VOSviewer software to visualize the network of keyword co-occurrences, authorship, and geographic distribution of publications. The analysis results show a significant increase in publications, particularly after 2021, reflecting growing scientific attention to dyscalculia in the context of mathematics learning difficulties and neurodevelopmental research. The thematic analysis identified five main clusters: cognitive, pedagogical, psychological, demographic, and theoretical, which are interconnected and demonstrate that dyscalculia is understood as a multifactorial disorder involving both cognitive and instructional aspects. Furthermore, research contributions are still dominated by developed countries such as the United States and the United Kingdom, although contributions from Indonesia and other developing countries are increasing. These findings underscore the importance of interdisciplinary collaborations integrating neuroscience, pedagogy, and technology as a foundation for developing inclusive, evidence-based learning interventions for students with dyscalculia.